Regional tax effort in Spain - Anabel Zárate Marco; Jaime Vallés Giménez (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
This work examines in depth the hypotheses explaining the tax capacity of regional governments, also determining their tax effort and explanatory factors. The study is done for the Spanish regions, using different techniques which have rarely been applied in this area. The results show that these jurisdictions have exercised their tax autonomy responsibly, in response to different budget and demographic factors and to the economic cycle. Also, an asymmetrical tax behaviour linked to income is observed: some regions have practically exhausted the possibilities of current sub-central taxes, while others still have ample fiscal space.
http://dx.doi.org/10.7910/DVN/8JY1NZ
Keywords: H71; H2; C23; C51; 330; regional tax effort; regional taxes; tax potential; frontier techniques